PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR DISPOSISI MATEMATIS SISWA SEKOLAH MENENGAH - Hairunisa, Namira; Zubaidah, Zubaidah; Ahmad, ,Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe results of observations by  researcher?s analysis at school about mathematical disposition students get less attention from the teacher. It is because there is not tools to measure stufent?s methematical disposition.  The main purpose of this research is the discovery of student?s methematical disposition instruments that already have validity and high realibilty. The subject of this research are student?s from SMK-SMTI pontianak, as amounted to 261 student?s/ the development procedure of this Research and Development (R&D)  with data analysis technique such as content validity by panelist, panelist compabiltity construst validity, item validity, and relibility coefisien. All of content validity by panelist are valid. The reliability of panelst conformity is reliable because of the founded of the matemathical disposition instrument of 45 statements is 0,936. The school is obtained exact?y 12 indicators with 3 statements eliminated on construct validity. Furhermore, based on the result afte trial usage, there are 42 items valid and the reliability coeffisient is 0,911.It can be conclude that the instruments for mensuring mathematical disposition of high school students os already standard and reliable. Thus the developed mathematical disposition instrument is eligible to be used in capturing  data on mathematical disposition of middle school student?sKeyword: Instrument Development, Mathematical Disposition